2023
DOI: 10.3390/f14091699
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variation in Vegetation Response to Runoff in the Ebinur Lake Basin

Chenglong Yao,
Yuejian Wang,
Guang Yang
et al.

Abstract: The response of spatial and temporal vegetation changes to runoff is a complex process involving the interaction of several factors and mechanisms. Timely and accurate vegetation and runoff change information is an important reference for the water cycle and water resource security. The Ebinur Lake Basin is representative of arid areas worldwide. This basin has been affected by climate change and human activities for a long time, resulting in the destruction of the basin’s ecological environment, and especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Due to the unique climatic conditions and resource constraints, ecosystem services have become a core area of ecological research in arid areas, involving water resource management, the carbon cycle, and climate regulation. By using the InVEST model, Yao et al [15] studied the spatial and temporal response of vegetation to runoff changes in the Ebinur Lake Basin by using remote sensing data. The results suggested that the spatial distribution of runoff was positively correlated with altitude.…”
mentioning
confidence: 99%
“…Due to the unique climatic conditions and resource constraints, ecosystem services have become a core area of ecological research in arid areas, involving water resource management, the carbon cycle, and climate regulation. By using the InVEST model, Yao et al [15] studied the spatial and temporal response of vegetation to runoff changes in the Ebinur Lake Basin by using remote sensing data. The results suggested that the spatial distribution of runoff was positively correlated with altitude.…”
mentioning
confidence: 99%